The Nonviolent Cross: Lonergan and Girard on Redemption - Doran, Robert M. (Theological studies, 2010)
Bernard Lonergan and René Girard provide succinct statements of the meaning of redemption. The article, having raised the question as to how the statements relate to one another, argues that Lonergan provides a heuristic structure for understanding redemption, while Girard supplies much of the data that the heuristic structure would organize. Complementarities between the two thinkers are highlighted, along with a few differences.